Cutaneous Mycobacterium goodii infection in an immunocompetent cat in Louisiana: clinical presentation, molecular identification, antimicrobial susceptibility and management. Issue 1 (April 2022) - Wu, Chi-Yen; Diaz, Sandra; Ellis, Angela; Jones, Rebekah; Pucheu-Haston, Cherie
Case summary: A 9-year-old spayed female domestic shorthair cat was presented to a referral hospital for management of recurring non-healing ulcerations and a subcutaneous mass on the ventral abdomen. Prior treatment included antibiotics (cefovecin followed by clindamycin), wound cleaning and surgical debulking, but the ulcerations and mass recurred 1 month after surgical removal. At this point, the cat was started on doxycycline and pradofloxacin and referred for further work-up. The culture of skin biopsy specimens obtained at the time of referral revealed a population of bacterial colonies with two distinctly different phenotypes. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and 16S rRNA gene sequencing identified both colonies as Mycobacterium goodii . A diagnosis of a cutaneous infection of rapidly growing mycobacteria was made, and treatment with oral pradofloxacin and doxycycline was initiated. The ulcerations resolved within 4 months, and the subcutaneous mass gradually decreased in size until it was no longer palpable, even 4 months after the cessation of antibiotics. Relevance and novel information: This is the second reported feline cutaneous M goodii infection in North America. The organism was not visualized on histopathology but was successfully cultured from tissue obtained by skin punch biopsy. A phenotypic switching phenomenon affecting the susceptibility results was suspected, possibly explaining the presence of phenotypically different but genetically identical strains. This case highlights the importance of submitting aseptically obtained tissue, fluid or fine-needle aspirates for culture and species identification, as well as histopathology, when infection with higher bacteria, such as rapidly growing mycobacteria, is suspected.